Towards a pluralistic conception of research methods in information systems research - Ulrich Frank (Universität Duisburg-Essen, Institut für Informatik und Wirtschaftsinformatik (ICB), 2006)
There has been an ongoing debate about the use of research methods in Information Systems Research (ISR). Despite the international dominance of the behaviourist approach, there is a remarkable number of researchers who propagate alternative methods, such as hermeneutic approaches or the so-called Design-Science approach. This report is based on the assumption that the variety of research topics and objectives of ISR cannot be covered in a satisfactory way by one method. Instead, it is claimed that there is need for the configuration of methods according to individual research designs. For this purpose, the report is focussing on the peculiarities of ISR in order to develop the requirements a research method should serve. Subsequently, existing methods, such as the behaviourist, the hermeneutic or the Design Science approach are evaluated with respect to these requirements. To develop a common conception of science that fits all disciplines and can be adapted to serve the peculiarities of ISR at the same time, the report gives an overview of selected approaches in philosophy of science. Against this background, a conceptual framework is developed that guides the configuration of individual research methods. It includes the core concepts that constitute the parameters of configuration and supplemental criteria to support configuration decisions. Finally, the framework is adapted to serve as a conceptual foundation for the unified documentation of research results. It fosters comparability of research contributions across the spectrum of possible research methods and contributes to the reconstruction of scientific progress.
Keywords: 650; Informationssystem; Wirtschaftsinformatik; Wissenschaftstheorie